Grammatical number processing and anticipatory eye movements are not tightly coordinated in English spoken language comprehension - Riordan, Brian; Dye, Melody; Jones, Michael N. (Frontiers in Psychology, 2015)
Recent studies of eye movements in world-situated language comprehension have demonstrated that rapid processing of morphosyntactic information – e.g., grammatical gender and number marking – can produce anticipatory eye movements to referents in the visual scene. We investigated how type of morphosyntactic information and the goals of language users in comprehension affected eye movements, focusing on the processing of grammatical number morphology in English-speaking adults. Participants’ eye movements were recorded as they listened to simple English declarative (There are the lions.) and interrogative (Where are the lions?) sentences. In Experiment 1, no differences were observed in speed to fixate target referents when grammatical number information was informative relative to when it was not. The same result was obtained in a speeded task (Experiment 2) and in a task using mixed sentence types (Experiment 3). We conclude that grammatical number processing in English and eye movements to potential referents are not tightly coordinated. These results suggest limits on the role of predictive eye movements in concurrent linguistic and scene processing. We discuss how these results can inform and constrain predictive approaches to language processing.